2013
DOI: 10.5714/cl.2013.14.2.094
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of isotropic pitch-based carbon fiber

Abstract: Isotropic pitch fibers were stabilized and carbonized for preparing carbon fibers. To optimize the duration and temperature during the stabilization process, a thermogravimetric analysis was conducted. Stabilized fibers were carbonized at 1000, 1500, and 2000°C in a furnace under a nitrogen atmosphere. An elemental analysis confirmed that the carbon content increased with an increase in the carbonization temperature. Although short graphitic-like layers were observed with carbon fibers heat-treated at 1500 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…According to previous reports, the crystallinity of PANbased and aramid-based CFs increased as the carbonization temperature increased [10,11]. However, the crystallinity of pitch-based CFs exhibited an opposite trend in carbonization temperatures below 1000 o C [9,[14][15][16]. Namely, the crystallinity of the pitch decreased with carbonization temperatures in the range of 700-1000 o C; however, it increased eventually with a further increase in the carbonization temperature over 1000 o C. A proper explanation about this phenomenon could hardly be found.…”
Section: Characterization Of the Carbonized Pitch Fiber And Carbonizementioning
confidence: 75%
See 1 more Smart Citation
“…According to previous reports, the crystallinity of PANbased and aramid-based CFs increased as the carbonization temperature increased [10,11]. However, the crystallinity of pitch-based CFs exhibited an opposite trend in carbonization temperatures below 1000 o C [9,[14][15][16]. Namely, the crystallinity of the pitch decreased with carbonization temperatures in the range of 700-1000 o C; however, it increased eventually with a further increase in the carbonization temperature over 1000 o C. A proper explanation about this phenomenon could hardly be found.…”
Section: Characterization Of the Carbonized Pitch Fiber And Carbonizementioning
confidence: 75%
“…CF process techniques consist of fiber spinning, stabilization, and carbonization, and the effects of fiber spinning and thermal processes on fiber structure have been widely investigated. Although previous studies have mostly focused on the stabilization process [4][5][6][7][8], there have been only a few reports focusing on the carbonization process [8][9][10][11]. During the carboniza-flow in a temperature range of 500-1100 o C to compare the effect of the carbonization temperature on the crystallinity of the pitch samples with different forms (fiber and powder).…”
Section: Introductionmentioning
confidence: 99%
“…It is found that a significant weight was gained in the stabilized fibers (≈10.5%) because oxygen atoms diffuse into the fibers to induce thermosetting [23]. This crosslinking reaction helps the fibers maintain their shape and allows them to be carbonized in the following process without inter-filament fusing [24]. It is interesting to note that the fibers having graphene exhibit lower stabilization yield than that of the neat pitch-based fiber.…”
Section: Resultsmentioning
confidence: 99%
“…The production of carbon fiber from pitch can result in cost reductions or very high properties with an additional processing step. Therefore, efforts to produce carbon fiber using pitch have flourished in recent years [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%